Prevalence and perceived severity of post-traumatic stress disorder among flood victims in Kuala Terengganu, Malaysia - San San, Oo; Rohayah, Husain; Rahmah, Mohd Amin (Malaysian Public Health Physicians Association, 2016)
Floods can lead to direct economic and property losses and result not only in physical injuries and deaths but also in psychological trauma. Post-traumatic stress disorder (PTSD) is a commonly used indicator to evaluate psychological injuries after disaster. This study aimed to determine the relationship between PTSD prevalence and related perceived severity of post flood impact by economical, non-economical and flood status severity domains besides relevant socio-demographic factors according to gender specific analysis. This cross-sectional study was conducted among community in Kampung Hulu Takir, Kuala Terengganu, Malaysia in 2015 two weeks after flood. It included a total of 98 males and 110 females aged 18 years and above. Data was collected by interview-guided questionnaire to determine the prevalence of PTSD. SPSS version 21.0 was used for analysis of the relationship between socio demographic factors, perceived economic, non-economic and flood severity with PTSD. Finally chi square test was used to assess the predictors of PTSD according to gender. The prevalence of PTSD was 9.2% in males and 10.9% in females, giving a total of 10.1%. Significantly higher prevalence of PTSD was found in severely perceived economic and flood impact categories (33.3% and 23.8% in males; 23.8 % and 37.5% in females) and giving in overall 44.0% and 31.3 % respectively. Effective PTSD management strategies targeting females post flood victims who severely perceived economically and nature flood impact should be implemented in order to prevent further consequences of PTSD.